Cotard's syndrome and delayed diagnosis in Kashmir, India - Wani, Zaid A (BioMed Central, 2008)
Cotard's syndrome is a rare syndrome, characterized by the presence of nihilistic delusions. The syndrome is typically related to depression and is mostly found in middle-aged or older people. A few cases have been reported in young people with 90% of these being females. We present a case of a young pregnant woman suffering from Cotard's syndrome. This is the first report of this syndrome in a pregnant woman. The case was diagnosed late, due to lack of awareness of psychiatric problems in primary care physicians resulting in undue suffering, loss of precious time and resources for the patient. Besides highlighting the rare combination of pregnancy and Cotard's syndrome this report delineates the difficulties faced by patients with such symptoms in a low resource setting.